Alignment between Business Requirement, Business Process, and Software System: A Systematic Literature Review. (1st October 2019) - Habba, Maryam; Fredj, Mounia; Benabdellah Chaouni, Samia
Abstract : Alignment is a very wide subject that can be used to support an organization's information system. Many authors have dealt with this topic according to various dimensions, including the operational alignment dimension. Our work aims to review approaches that discuss the operational alignment by reducing the gap between business requirement, business process, and software system. Therefore, this study was conducted by a systematic literature review (SLR). In the first step, we gather 1846 papers relative to the subject. In the last step, we filter those articles and select only the most pertinent ones, which leave us with 63 studies to focus on. These primary studies were analyzed according to 9 quality assessment criteria.